2017
DOI: 10.3389/fmicb.2017.02287
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the CrbS/R Two-Component System in Pseudomonas fluorescens Reveals a New Set of Genes under Its Control and a DNA Motif Required for CrbR-Mediated Transcriptional Activation

Abstract: The CrbS/R system is a two-component signal transduction system that regulates acetate utilization in Vibrio cholerae, P. aeruginosa, and P. entomophila. CrbS is a hybrid histidine kinase that belongs to a recently identified family, in which the signaling domain is fused to an SLC5 solute symporter domain through aSTAC domain. Upon activation by CrbS, CrbR activates transcription of the acs gene, which encodes an acetyl-CoA synthase (ACS), and the actP gene, which encodes an acetate/solute symporter. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(48 citation statements)
references
References 65 publications
(77 reference statements)
5
43
0
Order By: Relevance
“…The presence of crbR significantly increased lacZ expression ( Fig. 5A), consistent with crbR directly activating acs expression, as observed in V. vulnificus and Pseudomonas (22,28).…”
supporting
confidence: 82%
See 2 more Smart Citations
“…The presence of crbR significantly increased lacZ expression ( Fig. 5A), consistent with crbR directly activating acs expression, as observed in V. vulnificus and Pseudomonas (22,28).…”
supporting
confidence: 82%
“…5B and C), which may include the binding site targeted by CrbR. A previous study identified a putative CrbR binding site, with the primary consensus depicted as GAC(N 4 )GTC (28). Within the 15-bp region that we identified lies the sequence TCC(TAAA)GTCT (boldface indicates base pairs that match with the consensus CrbR binding site), which could act as the binding target.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Similar to the transcriptomics approach, targets for RRs may be identified by measuring protein abundances between WT and mutant strains. Proteomics studies are often accompanied by transcriptomics, metabolomics or ChIP‐seq analyses (Wang et al ., , ; Sepulveda and Lupas, ; Sun et al ., ; Reed et al ., ).…”
Section: Expression Profiling Methodsmentioning
confidence: 99%
“…The STAC domain is suggested to mediate interactions with other proteins or control the transport cycle of the SLC5 domain 12 . It follows a PAS domain (about 115 amino acids) that may bind a yet to be identified signal molecule, a dimerization and histidine phosphotransfer domain (DHp, about 65 amino acids), and a catalytic ATP-binding domain CA (about 115 amino acids) 13 . The individual domains are connected by linker sequences (Fig.…”
mentioning
confidence: 99%